A novel thymoma-associated autoimmune disease: Anti-PIT-1 antibody syndrome - Bando, Hironori (Sci Rep, 2017)
Anti-PIT-1 antibody syndrome has recently been reported and characterized by acquired growth hormone (GH), prolactin (PRL), and thyroid-stimulating hormone (TSH) deficiencies associated with autoimmunity to a pituitary specific transcription factor PIT-1, which plays an essential role in GH-, PRL-, and TSH-producing cells. Although circulating anti-PIT-1 antibody and PIT-1-reactive cytotoxic T cells (CTLs) were detected in the patients, the pathophysiology and precise mechanisms for the autoimmunity remain unclarified. During the follow up, thymoma was diagnosed in all 3 cases with anti-PIT-1 antibody syndrome. Immunohistochemical analysis revealed that PIT-1 was strongly expressed in neoplastic cortical thymic epithelial cells. Importantly, after thymectomy, the titer of anti-PIT-1 antibody decreased and reactivity of CTLs toward PIT-1 diminished. These data strongly suggest that the aberrant expression of PIT-1 in the thymoma plays a causal role in the development of this syndrome. Thus, we define that this syndrome is a novel thymoma-associated autoimmune disease.